2009
DOI: 10.1111/j.1600-0897.2009.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Identification of Toll‐Like Receptors in the Rat (Rattus norvegicus): Messenger RNA Expression in the Male Reproductive Tract Under Conditions of Androgen Variation

Abstract: Tlr5, Tlr10, and Tlr11 are ubiquitously expressed in the rat. Tlrs seem to be expressed during male reproductive tract development and under conditions of androgen ablation, suggesting the preparedness of the male reproductive tract to detect an infection under all conditions of androgen status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…784 In rat seminal vesicles, mRNA for TLR2, 5,6,7,8,9,10, and 11 were highly expressed, with low levels of the remaining TLRs. 776 Notably, expression of CD14 was higher in the prostate and seminal vesicles of the rat than in any other tissue of the male reproductive tract. 443 Studies have shown that sequence variants in TLR4 and the TLR1-TLR6-TLR10 gene cluster in the human are associated with an increased risk of prostate cancer, suggesting a link between susceptibility to inflammation and tumorigenesis in this organ.…”
Section: Production and Actions Of Inflammatory Mediatorsmentioning
confidence: 93%
See 1 more Smart Citation
“…784 In rat seminal vesicles, mRNA for TLR2, 5,6,7,8,9,10, and 11 were highly expressed, with low levels of the remaining TLRs. 776 Notably, expression of CD14 was higher in the prostate and seminal vesicles of the rat than in any other tissue of the male reproductive tract. 443 Studies have shown that sequence variants in TLR4 and the TLR1-TLR6-TLR10 gene cluster in the human are associated with an increased risk of prostate cancer, suggesting a link between susceptibility to inflammation and tumorigenesis in this organ.…”
Section: Production and Actions Of Inflammatory Mediatorsmentioning
confidence: 93%
“…The TLRs are found throughout the epithelium, and in immune cells, of the posttesticular reproductive tract. 109,[441][442][443][444]776 Studies in the rat and mouse have produced some conflicting data, but overall indicate that expression levels of TLR1-6 in the epididymis are similar to those found in the testis, with expression progressively declining toward the vas deferens. On the other hand, expression of TLRs 7, 9, and 11 tends to be higher in the epididymis and vas deferens than in the testis (Table 19.4).…”
Section: Production and Actions Of Inflammatory Mediatorsmentioning
confidence: 99%
“…Signalling pathways effected by these receptors promote the production of antimicrobial proteins and peptides, and these processes are well characterised in reproductive and in other organ systems (Mukherjee, Karmakar, & Babu, ). We and other groups demonstrated the abundant expression of Tlr1‐13 in the male reproductive tract of different species (Biswas et al, ; Biswas & Yenugu, ; Liman, Alan, & Apaydin, ; Palladino, Johnson, Gupta, Chapman, & Ojha, ; Palladino, Savarese, Chapman, Dughi, & Plaska, ; Pioli et al, ). The general gene expression pattern and LPS/uropathogenic Escherichia coli ‐mediated induction of rat Defb s and DEFB‐like proteins and peptides belonging to the Sperm‐Associated Antigen 11 (SPAG11) family were reported in the male reproductive system (Biswas & Yenugu, , , ; Yenugu, Chintalgattu, et al, ; Yenugu, Hamil, French, & Hall, ).…”
Section: Introductionmentioning
confidence: 60%
“…The prediction might be helped when genes of TLR11 from more species were analyzed. TLR11 is present in the mouse and rat genomes but not in the genomes of cat, dog, frog, chimp and fugu [ 16 , 41 ]. Thus, we can imagine the evolutionary pressures that cause TLR11 to downgrade to a non-coding gene in humans and certain animals.…”
Section: Discussionmentioning
confidence: 99%